2021
DOI: 10.1002/14651858.cd010070.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Altered dietary salt intake for people with chronic kidney disease

Abstract: 2. Art. No.: CD010070. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 115 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…Salt restriction with adequate protein and calorie intake is important in all stages of CKD, and in dialysis patients in particular. Recent reviews and meta-analyses support the benefits of salt reduction [94][95][96]. Nutritional (salt) management needs to be adjusted for individual lifestyle, dietary habits, and available food types [97], as the elderly population is increasing rapidly in both Japan and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Salt restriction with adequate protein and calorie intake is important in all stages of CKD, and in dialysis patients in particular. Recent reviews and meta-analyses support the benefits of salt reduction [94][95][96]. Nutritional (salt) management needs to be adjusted for individual lifestyle, dietary habits, and available food types [97], as the elderly population is increasing rapidly in both Japan and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…We estimate that achieving the NPHS and SDT for sodium intake could reduce average systolic BP of adult Australians by 1.7 mmHg and 2.1 mmHg respectively. High certainty evidence from a recent Cochrane meta-analysis showed that salt reduction of 4.2g/day (1,640mg of sodium) in people with CKD decreased systolic BP by 6.9 mmHg, and also reduced albuminuria by 36% (10). Studies have shown that the effect of high sodium intake on BP are greater in people with CKD compared to the general non-CKD population, due to decreased renal excretion of the excess sodium (8, 33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we account for the differential impact of salt reduction in people with and without hypertension in line with evidence of the stronger effects of sodium on BP in those with hypertension (4, 7, 26). Third, there is limited empirical evidence on the longterm effects of sodium intake on CKD, echoed in a recent Cochrane meta-analysis (10). Our modelling compliments this evidence gap by projecting beyond intermediate outcomes (blood pressure) to CKD for the first time in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the potential benefits of restricting salt intake are still discussed. Nevertheless, several studies and some meta-analyses have suggested that lowering sodium intake delays renal disease progression [ 38 40 ]. Recently, an open-label, cluster-randomized trial, the SSaSS study, including older adults with a history of stroke or high BP, has demonstrated prospectively the benefits of reducing sodium and increasing potassium intake in terms of CV morbidity [ 41 , 42 ].…”
Section: Management Of Hypertension In Ckdmentioning
confidence: 99%